Efeito do tamanho e da poda de mudas no rendimento da cebola (Allium cepa L.) - da Silva, José Francisco; Ferreira da Silva, Roberto; do Vale Rodrigues, Joaquim Joel (Revista Ceres, 2025)
This experiment was conducted onthe experimental farm of the Departament of Fitotecnia of the Universidade Federal de Viçosa, Minas Gerais, in 1970.